PERAN KONTROL DIRI DALAM SELF-DISCLOSURE DI KALANGAN GENERASI Z PENGGUNA TIKTOK - Nawangsari, Sri; Huda, Nurul; Aulia Puspita, Arnetta Dinda (KAGANGA KOMUNIKA: Journal of Communication Science, 2024)
An individual's effort to express their feelings, emotions, and personal data to others is known as self-disclosure, while self-control is the ability to manage one's emotions, thoughts, and behavior in order to avoid conflict and encourage positive actions. This study aims to examine the impact of self-control on self-disclosure among Generation Z TikTok users. The research method is quantitative, using incidental sampling, and data was collected through a questionnaire with Likert scale measurements distributed to 300 respondents. The study employs simple regression analysis with the help of the Statistical Packages for Social Science (SPSS) version 22.0 for Windows to understand the influence of self-control on self-disclosure in Gen Z TikTok social media users. The hypothesis test results show a high significance with a value of 0.000 (p<0.01) and an F table value of 3.87, indicating that the hypothesis is accepted because the calculated F value is greater than the F table value. This suggests a strong influence of self-control on self-disclosure. The R² value of 0.569 indicates that self-control influences self-disclosure by 56.9%, while the remaining 43.1% is influenced by factors outside the scope of the study. Based on the self-control variable viewed by the respondent's gender, it was found that gender does not affect the level of self-control. Meanwhile, the age category suggests that a stable age period requires good self-control to face external challenges. Keywords: Self-Control, Self-Disclosure, Generation Z, TikTok